Sindrom Brugada: Diagnosis dan Tatalaksana - Reza Octavianus; Yoga Yuniadi (The Indonesian Heart Association, 2012)
Brugada syndrome associated with high incidence of sudden death in young and otherwise healthy adults in many parts of the world. The Brugada syndrome which is characterized by an ST-segment elevation in the right precordial ECG leads, is a familial disease that displays an autosomal dominant mode o? transmission with incomplete penetrance. The first and only gene to be linked to Brugada syndrome is SCN5A, the gene that encodes for the subunit of the cardiac sodium channel gene. More than 80 mutations in SCN5A have been linked to the syndrome.Based on ECG characteristics the syndrome divided into three types. Brugada syndrome is definitively diagnosed when a type 1 ST-segment elevation is observed in >1 right precordial lead (V1 to V3) in the presence or absence of a sodium channel– blocking agent, and in conjunction with one of the following: documented ventricular fibrillation (VF), polymorphic ventricular tachycardia (VT), a family history of sudden cardiac death at < 45 years old, coved-type ECGs in family members, inducibility of VT with programmed electrical stimulation, syncope, or nocturnal agonal respiration. Currently, an implantable cardioverter defibrilla?or (ICD) is the only proven effective treatment for the disease.